KEKUATAN MODAL DAN PERILAKU KEKERASAN NEGARA PADA MASA ORDE BARU DAN PASCA ORDE BARU: STUDI KASUS FREEPORT - Adrianus Bintang Hanto Nugroho (Cakrawala Jurnal Penelitian Sosial, 2014)
This article aims to explain how the Freeport as capital strength affects the violent acts committed by the State. During the New Order State provide physical protection against Freeport takeover of customary lands of the Amungme for its mining interests. Various rejection Amungme tribal performed on Freeport's presence in their customary land were met with violence by the State. Acts of violence by the state persists even after the fall of the New Order. However, the target of violence no longer citizens of the Amungme but shifted into the traditional gold miners and laborers Freeport itself.The author uses the theory states that introduced Ralph Miliband to explain how a capital strength as Freeport can influence violent behavior State. According to Miliband capitalist class, namely the power of capital or corporations, with their economic power can use the state as an instrument to meet its interests. By colonizing the elite countries, corporations can influence the formation of policies that favor.In the context of colonization Freeport done through how to build a close relationship with the elite of the country. The close relationship was built through two different ways. During the New Order Freeport tend to take a more subjective nature as a way to build good personal relationships with the elite of the country, to finance the cost of their holiday, and make business deals that made them rich. Post-New Order Freeport tend to take a more objective in nature such as making payments formally through corporate social responsibility programs and fund development projects in the Mimika Regency.The fall of the New Order makes Freeport should change its approach from that pattern tends to be subjectively be obyektif.Hal shows that the capitalist class which is embodied in the form of a corporation can adapt well to the changes that occur in a state system. Both in the state system of authoritarian or democratic, in fact the ruling capitalist class (rule) even though they are not directly rule (govern).Keywords: Capital strength, State, Colonization, Freeport, State Violence